NEUTRALITY IN CONFLICT MEDIATION PROCESS - Syaiful Anam (Dauliyah Journal of Islamic and International Affairs, 2020)
In conflict mediation understanding the concept and mastering the skill of neutrality is perceived as essential. Despite as a fundamental and core principle in mediation, it has been a debate among mediators upon the outcome of the mediation itself. This principle puts mediator as facilitator who would not influence or be partial over the parties. Indeed, mediators highly respect on aspirations and demands of the parties by creating an acceptable procedural framework which enables disputants to achieve their goals fairly. Nevertheless it is practically an arduous principle and inapplicable. In addition, neutrality is not a stipulation for a successful mediation; rather, mediators need to and should be partial and biased in some cases. This article, therefore, is aimed to examine the problems revolve around the issues of neutrality in mediation process.